Dual-Source Computed Tomography of the Chest in Blunt Thoracic Trauma: Reduced Aortic Motion Using a Novel Temporal Resolution Optimization Method. Issue 6 (November 2019) - Liang, Teresa; McLaughlin, Patrick D.; Nugent, James P.; Rai, Shamir; Schmiedeskamp, Heiko; Louis, Luck; Khosa, Faisal; Nicolaou, Savvas
Abstract : Purpose: The purpose of this study was to evaluate the clinical utility of temporal resolution optimization (TR-Opt), a computed tomography (CT) postprocessing technique, in reducing aortic motion artifacts in blunt thoracic trauma patients. Materials and Methods: This was an IRB-approved study of 61 patients with blunt thoracic trauma carried out between February 18 and September 6, 2014; the patients had been imaged using a standardized dual-source high-pitch (DSHP) CT protocol. Image raw data were retrospectively postprocessed using the TR-Opt algorithm (DSHP-TR-Opt) and compared with conventional images (DSHP). Diagnostic ability to confidently identify and exclude potential injuries and qualitative aortic motion artifacts using a 5-point Likert scale (1=absence of motion artifacts; 5=severe motion artifact) was graded by 2 readers at multiple thoracic locations. Signal-to-noise and contrast-to-noise ratios were generated as quantitative indices of image quality. Results: Motion artifacts degrading interpretation and limiting diagnosis of aortic injuries were present in 45% (442/976) of the assessed regions on DSHP. TR-Opt algorithm eliminated motion artifacts in 85% of the motion-degraded areas (375/442), leaving persistent motion artifacts in only 15% (67/442). Motion artifacts were most improved at the interventricular septum (1±1 vs. 3±1), aortic valve (2±1 vs. 4±1.5), and ascending aorta (1±1 vs. 3±2, P <0.005). Mean aorta noise (NAo ) was 41.7% higher in the DSHP-TR-Opt images (26.5 vs. 18.7 HU, P <0.0001). Conclusions: Temporal resolution optimized reconstruction is a raw data–based CT postprocessing technique that can be used to remove the majority of thoracic aortic motion artifacts that commonly degrade interpretation when imaging blunt thoracic trauma patients.